Theoretical and experimental analysis of solar enclosure as part of energy-efficient house - Shapoval, Stepan; Zhelykh, Vasyl; Venhryn, Iryna; Kozak, Khrystyna; Krygul, Roman (Eastern-European Journal of Enterprise Technologies, 2019)
The use of solar energy as a potential alternative source to ensure the heat supply to energy-efficient houses was explored. We have performed preliminary theoretical analysis of energy indicators for the combined heat supplying system when a solar window is used as part of the enclosure for an energy efficient house. In order to enhance operational effectiveness of the studied plant relative to existing solar collectors and to improve it in the structural aspect, the stratification of a heat carrier in the tank-accumulator of the combined heat supply system with a solar window was calculated. The study of operational efficiency of the experimental setup for using solar energy was carried out under the mode of circulation and gravitational motion of the heat carrier by the intensity of radiation of the solar energy simulator on the system of 600 W/m2 and 900 W/m2. Water was used as a heat carrier. We have analyzed changes in temperature of the heat carrier in the solar collector and in the tank-accumulator of the proposed combined solar heat supply system with a solar window as part of the external enclosure of an energy-efficient house. It was established that the heat carrier temperature under the circulation mode reached 26.5 °C. We have also presented comparative field, laboratory, and theoretical calculations of the average temperature of the heat carrier in the tank-accumulator under the mode of the heat carrier gravitation motion under various conditions. Efficiency of the experimental setup was calculated. The dynamics of change in efficiency of the solar heat supply system with a solar window were described. Efficiency was ≈55 % under the mode of heat carrier circulation for heat energy accumulation in the tank-accumulator, depending on heating duration. Under the mode of gravitational motion of the heat carrier, we calculated efficiency for the design of a solar window only, which was 53 %